The effects of e-learning vs. gamification-based training on ICU nurses’ knowledge and attitudes toward organ donation candidates: a study based on the psychological security and empowerment model - Meysam Pour Hossein; Mojgan Ansari; Nazanin Fekri; Hamideh Yazdimoghaddam (BMC Medical Education)
Abstract Background Effective training of nurses who manage candidates for organ donation is a critical issue that can enhance nurses’ knowledge and attitudes, ultimately improving the quality and efficiency of donated organs. This study aims to compare the effects of e-learning and gamification-based training on ICU nurses’ knowledge and attitudes toward organ donation candidates based on the Improving Psychological Security and Empowerment (IPSE) model. Methods This clinical trial used a pre- and post-intervention design with three groups and was conducted on 45 ICU nurses. Participants were randomly assigned to one of three groups: e-learning, gamification-based training, and a control group (15 participants per group). The e-learning group attended two two-hour webinars based on the IPSE model. After reviewing educational materials prepared based on the IPSE model, the gamification group completed six scenarios via email. The control group received no intervention. A questionnaire assessing the nurses’ knowledge and attitudes toward the care of organ donation candidates was administered before and after the intervention. To evaluate the retention of learning, the same questionnaire was completed again one month after the intervention. Data analysis was performed using mixed- ANOVA in SPSS (version 26) and R (version 4.1.2). The assumptions of mixed-ANOVA were checked. In both knowledge and attitude modeling, the normality assumption was confirmed by gg-plot. The homogeneity of variances assumption was tested and confirmed by Levene test. The sphericity assumption for the time effect as well as the interaction effect of time and group was tested and rejected, and we used Greenhouse–Geisser correction P-value. Results The results revealed that, after the intervention, participants’ mean knowledge scores increased significantly in both the e-learning and gamification groups. The score of the e-learning group (Group 1) rose from 9.33 to 14.86, while in the gamification group (Group 2), it increased from 8.87 to 18.00. Both groups demonstrated statistically significant improvements in knowledge scores (P < 0.001). In the control group, the mean knowledge score increased from 9.93 to 12.80, which was also statistically significant (P < 0.001). Regarding attitudes, the e-learning group (Group 1) showed an increase in mean score from 45.73 to 56.86, while the gamification group (Group 2) improved from 47.33 to 61.46. Both groups exhibited statistically significant improvements in attitude scores post-intervention (P < 0.001). The control group’s mean attitude score also increased from 48.26 to 51.13, showing a statistically significant change (P < 0.001). Conclusion The results demonstrated that gamification-based training had a greater impact on nurses’ knowledge and attitudes than e-learning. Given the positive effects of both educational approaches, educational and medical center administrators should be familiarized with innovative approaches like gamification to enhance nurses’ learning by utilizing more engaging and practical methods.